2017
DOI: 10.1002/ptr.5774
|View full text |Cite
|
Sign up to set email alerts
|

Artichoke Leaf Extract Inhibits AKR1B1 and Reduces NF-κB Activity in Human Leukemic Cells

Abstract: The human intracellular enzyme AKR1B1 belongs to the aldo-keto reductase superfamily. The AKR1B1-catalyzed reduction of aldehydes is part of the intracellular inflammatory pathway leading to the activation of NF-κB and the expression of pro-inflammatory genes. The present study is aimed at determining the inhibition of AKR1B1 brought about by an extract of artichoke leaves (bracts), and the effects of this extract and three participating compounds on the expression of AKR1B1, COX-2, and MMP-2 proteins in THP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…In conclusion, the present study extends our previous work on biological activities of artichoke leaf extract (Miláčková et al, ) revealing antioxidant activity in cultured C2C12 cells exposed to high glucose. In addition, the extract effectively inhibited accumulation of sorbitol in the rat eye lenses exposed to high glucose ex vivo.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, the present study extends our previous work on biological activities of artichoke leaf extract (Miláčková et al, ) revealing antioxidant activity in cultured C2C12 cells exposed to high glucose. In addition, the extract effectively inhibited accumulation of sorbitol in the rat eye lenses exposed to high glucose ex vivo.…”
Section: Resultssupporting
confidence: 90%
“…The artichoke leaves are well known for their beneficial therapeutic effects in enhancing lipid metabolism, choleresis, and hepatic functions. In several studies, the extracts from artichoke leaves showed also decreasing activities of glucose level and beneficial effect on lipid metabolism of diabetic rats (Hosseini et al, ; Magied et al, ; Salem et al, ) as well as effective AKR1B1 and RL‐AKR inhibitions (Miláčková et al, ). Human AKR1B1 (and rat equivalent RL‐AKR) is the first enzyme of the polyol pathway that reduces glucose to sorbitol more intensively under diabetic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that the antioxidant activity of artichoke might be related to following compounds: (a) polyphenolics (caffeoylquinic acids and flavonoids) and (b) Sesquiterpenes (Ben Salem & Affes, ; Brown & Rice‐Evans, ; Gebhardt, ; Miccadei et al, ; Miláčková et al, ; Perez‐Garcia et al, ; Rahimuddin et al, ; Takei et al, ). 1.…”
Section: Disscusionmentioning
confidence: 99%
“…Polyphenolic compounds: (a) Caffeoylquinic acids: The chemical structure of caffeoylquinic acids is composed of one or two caffeic acid moieties and one quinic acid molecule. It is reported that cynarin (1,3‐O‐dicaffeoylquinic acid) and chlorogenic acid (5‐O‐caffeoylquinic acid), the most important caffeoylquinic derivatives in artichoke, would be partly responsible for antioxidant activity of artichoke (Gebhardt & Fausel, ; Miccadei et al, ; Miláčková et al, ; Pandino, Lombardo, Mauromicale, & Williamson, ; Perez‐Garcia et al, ). Recently, the antioxidant activity of chloregenic acid and cynarin was shown using various in vito antioxidant assays (Sato et al, ; Topal et al, ).…”
Section: Disscusionmentioning
confidence: 99%